ETHNOVETERINARY MEDICINE (EVM) - USING FRESH HERBALS FOR LIVESTOCK HEALTHCARE AT FARMERS’ LEVEL - Punniamurthy, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
EVM practices for mastitis, dermatitis, fowl pox and gastroenteritis are effectively employed in the field. Scientists increasingly recognize that traditional farmers have detailed knowledge of agriculture and animal husbandry. This knowledge is based on experience and observations. Traditional remedies are found to be effective and work for sound scientific reasons. Traditional veterinary practices offer a particularly rich resource for development. Cultivation and conservation of medicinal herbs is assured at the farmers’ level assuring participatory efforts. Many poor people derive their only income from harvesting medicinal plants. This income however, is probably declining where natural habitats are disappearing. A strategy that integrates conservation and cultivation of medicinal plants could create long-term employment and income opportunities. EVM seminars are organized for all stake holders including farmers, NGO and veterinarians and efforts are taken to promote the use of fresh herbs for primary health care of livestock. The package is based on the principles of Ethnoveterinary knowledge collected from the field. Efforts are taken to propagate the concept involving the stakeholders at all levels. Preliminary research is undertaken at the laboratory and field levels to validate the recipes. At least three recipes have been demonstrated at the field level and are successfully used by the farmers and veterinarians as well. The clinical conditions are mastitis, nonspecific gastroenteritis and dermatomycosis. Trainings are conducted for farmers, SHG women, field veterinarians and efforts are on to induct the EVM knowledge into the main stream veterinary curriculum.